Implications for Systemic Education-and Societal-Reform: A Discussion of McGranahan, Hobbs, Nachtigal, and Stephens - Robert D. Bhaerman (Journal of Research in Rural Education, 1994)
My task was to analyze these four articles with regard to their implications forrural school improvement. I began by asking, first, what are the major approaches to school improvement, and, second, how do the trends that were identified in rural America converge with or diverge from these approaches?